Energy Use-Trade Nexus. What Does the Data Set Say for Thailand? - JIRANYAKUL, Komain (Journal of Environmental Management and Tourism, 2016)
The main objective of this paper is to examine the relationship between energy use, exports, and imports in Thailand. The annual data from 1979 to 2012 are employed. The results from bounds testing for co-integration reveal that energy use is the main determinant of exports and imports. The results from short-run dynamics indicate that there is long-run causality running from energy use to exports and imports. Policy implication based upon the results of this study is that energy policy should be designed so as to generate sufficient energy for production in the exported and energy-intensive imported goods.However, trade and environmental problems should not be separable.
Keywords: Energy use; exports; imports; co-integration; causality